Analyzing the Millennials’ Intention towards Purchasing Reusable Shopping Bags (Evidence from Bali) - Antari, Ni Kadek Yuni; Pangaribuan, Christian Haposan (APPS Publications, 2021)
Objective – This study aims to analyze the millennials intention in Bali towards purchasing reusable shopping bags, the study extends the Theory of Planned Behavior (TPB). Methodology – The data were collected by using online questionnaire in Bali. The total sample of this study is 227 respondents. Findings – The finding of this study shows that Environmental Knowledge, Personal Belief, and Social Influence significantly affect the attitude of customers to purchase reusable shopping bags. Personal Belief becomes the dominant variable affecting consumer’s attitude. Meanwhile, Government Regulation and Media Exposure have no significant influence on the attitude towards purchasing reusable shopping bags. Attitude significantly influences Intention to Purchase reusable shopping bags, while Intention to Purchase reusable shopping bags gives a significant effect on Pro-Environmental Behavior. Novelty – In this study, the researchers extend the existing Theory of Planned Behavior and add environmental knowledge to show the fact that everyone is aware of the environment degradation issue and admit that the issue is everyone’s responsibility.